Comparative sphingolipidomic analysis reveals significant differences between doxorubicin-sensitive and -resistance MCF-7 cells. - Ola D A Shammout (Public Library of Science (PLoS), 2021)
Drug resistance is responsible for the failure of many available anticancer drugs. Several studies have demonstrated the association between the alteration in sphingolipids (SPLs) and the development of drug resistance. To investigate the association between SPLs metabolism and doxorubicin (dox)-resistance in MCF-7 cells, a comparative sphingolipidomics analysis between dox-sensitive (parental) and -resistant MCF-7 cell lines along with validation by gene expression analysis were conducted. A total of 31 SPLs representing 5 subcategories were identified. The data obtained revealed that SPLs were clustered into two groups differentiating parental from dox-resistant cells. Eight SPLs were significantly altered in response to dox-resistance including SM (d18:1/16), SM (d18:1/24:2), SM (d18:1/24:0), SM (d18:1/20:0), SM (d18:1/23:1), HexCer (d18:1/24:0), SM (d18:1/15:0), DHSM (d18:0/20:0). The current study is the first to conclusively ascertain the potential involvement of dysregulated SPLs in dox-resistance in MCF-7 cells. SPLs metabolism in dox-resistant MCF-7 cells is oriented toward the downregulation of ceramides (Cer) and the concomitant increase in sphingomyelin (SM). Gene expression analysis has revealed that dox-resistant cells tend to escape from the Cer-related apoptosis by the activation of SM-Cer and GluCer-LacCer-ganglioside pathways. The enzymes that were correlated to the alteration in SPLs metabolism of dox-resistant MCF-7 cells and significantly altered in gene expression can represent potential targets that can represent a winning strategy for the future development of promising anticancer drugs.